Pemberdayaan Masyarakat melalui Pengembangan Usaha Budidaya Ikan Gurami menggunakan Pendekatan ABCD di Yayasan Muslim Cendikia Bengkulu Tengah - Subhan, Subhan; Joyo, Harisman; Heriansyah, Heriansyah; Kohar, Abdul; Gunawan, Rolly; Wahyudi, Jarot; Asnaini, Asnaini (Yayasan Darussalam Bengkulu, 2023)
This research aims to build the economy at the Muslim Cendikia Foundation in order to strive to improve people's welfare, welfare will be realized if people's income increases. One of them is by doing entrepreneurship through empowering Gurami fish ponds which are expected to increase people's income. The method used is the ABCD (Asset Based Community Development) approach by emphasizing empowerment, understanding the potential and challenges that are owned to improve quality individually and in groups. The result of this community service is that in empowering the community through developing a gourami fish farming business by using the ABCD Approach at the Muslim Cendikia Foundation Bengkulu Tengah, the authors found that this fish pond asset is very promising for improving the community's economy, so that people are aware of this to plan design as well as possible in accordance with the instructions of the fisheries service. Management of gourami has been carried out starting with seeding as many as 10 thousand fish which will be harvested in the next 8-12 months.